Ruthenium(III) Catalyzed Oxidation of Fumaric Acid by Cerium(IV): A Kinetic and Mechanistic Approach - Kushwaha, Usha; Singh, A.K.; Singh, Amita (Asian Journal of Chemistry, 2012)
Kinetics of ruthenium(III) catalyzed oxidation of fumaric acid by acidic cerium(IV) has been studied by the rate of disappearance of [Ce(IV)]. The reaction is zero order with respect to [Ce(IV)] and unity with respect to both [fumaric acid] and [catalyst]. Negative effect of [H+] and inverse first order with respect to [Cl–] was observed while negligible effect of variation of [HSO4–] and ionic strength was observed. The result suggest the formation of a complex between substrate and hydroxylated species of ruthenium(III) in a fast step. This complex yields the product in a rate determining step. The complex reacts further with the acidic cerium(IV) species in a rate determining step to yield the products. The reaction constants involved in the mechanism and the activation parameters have been calculated. There is a good agreement between observed and calculated rate constants under different experimental conditions. Formic acid was detected as end product.